Analisis Korelasi Akuntabilitas dan Responsivitas dalam Implementasi Program SDGs di Kabupaten Jeneponto Tahun 2022-2024 - Lail, Hijrah; Fajar Putera, Arifin; Akmal Ibrahim, Muhammad; Ahmad, Badu; Susanti, Gita; Munandar, Aris; Amalia, Ayu (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study examines the relationship between Sustainable Development Goals (SDGs) achievement, government accountability, and responsiveness in Jeneponto Regency during the 2022-2024 period. Data were obtained from a public perception survey on service delivery (n = 120 respondents) using proportionate stratified random sampling, supported by secondary data from SDG achievement reports, the regional development plan (RPJMD), and SAKIP documents. The questionnaire was developed based on SAKIP accountability indicators and public service responsiveness frameworks, and was tested for validity and reliability. Pearson correlation analysis was conducted after meeting normality and linearity assumptions. The results reveal disparities in SDG progress, with notable improvements in education and health, while economic and environmental indicators lag behind. Government accountability remains at a moderate level, and responsiveness to citizen complaints is perceived as low. Significant positive correlations were found between SDG achievement and both accountability (r = 0.61) and responsiveness (r = 0.53), indicating that governance quality strongly shapes sustainable development outcomes. These findings highlight the need to strengthen SDG integration into local performance management systems and to enhance public service responsiveness as key prerequisites for accelerating sustainable development in Jeneponto.